Нарны зайн хагас дамжуулагч материалд үзүүлэх сансрын орчны нөлөөллийг тооцоолох нь - Sarnai Odsuren; Лувсанбат; Анар; Төртогтох; Бэгзсүрэн; Маргад-Эрдэнэ; Эрдэнэбаатар (Scientific transaction of the National University of Mongolia. Physics, 2022)
Nano-satellites, which transmit energy through solar cells, are widely used to study the cosmic environment. However, under the influence of cosmic rays and charged particles, solar elements wear out and decompose. Therefore, in this article, we have predicted and calculated how the dose of charged particles will affect the launch of the satellite and how its performance or current and voltage will decrease.